PENGEMBANGAN KAPASISTAS SUMBER DAYA MANUSIA DALAM PELAYANAN PUBLIK PADA DINAS TENAGA KERJA KABUPATEN PASURUAN - Agung Purdianto (Universitas Halu Oleo, 2021)
This paper aims to find out the Development of Human Resources Capacity in Public Service at the Pasuruan District Labor Office. The research method using qualitative approach is done scientifically, more descriptive, emphasizing the process rather than the public about improving the human resources of pasuruan community by the Pasuruan District Labor Office. The results showed that the Pasuruan District Employment Office implemented an increase in human resources developed according to the theory of capacity building in minimizing the unemployment rate, and as an effort to improve human resources precisely in the field of placement and expansion of labor (PENTA). The motivation, disciplinary and training is very influential to human resources and minimize the unemployment rate in Pasuruan Regency.